PELAGANDONG SEBAGAI BASIS PEMBINAAN KERUKUNAN UMAT BERAGAMA DI KOTA AMBON - abd kadir massoweang (Al-Qalam, 2007)
This research was conducted in Ambon, Maluku. The aim of research isto describe how Pelagandong as basic on social harmony constructionin Ambon society. This research used qualitative method, where datawas collected by depth interview. Than data was analyzed by descriptive-qualitative.This research showed that Pelagandong is a social instrument in constructingsocial harmony and unity between a community to other community,a village to other village with different background and socialhabit. Today, Pelagandong still have a good role and position in Ambonsociety.